ISwathX 2.0 for Processing DDA Spectral Libraries for DIA Data Analysis. Issue 1 (1st June 2020) - Noor, Zainab; Mohamedali, Abidali; Ranganathan, Shoba
Abstract: The iSwathX web application processes and normalizes mass spectrometry−based proteomics spectral libraries generated in the data‐dependent acquisition (DDA) approach. These libraries are stored in various proteomics repositories such as PeptideAtlas and NIST, or are user‐generated and provide reference data for data‐independent acquisition (DIA) targeted data extraction and analysis. iSwathX 2.0 can efficiently normalize DDA data from different instruments, gathered at different instances, and make it compatible with specific DIA experiments. Novel functions for parallel processing of DDA libraries and DIA report files, along with various data visualizations, are available in iSwathX 2.0. The step‐by‐step protocols provided here describe how the libraries are uploaded, processed, visualized, and downloaded using various modules of the application. They also provide detailed guidelines on the use of DIA report files for data analysis and visualization. © 2020 Wiley Periodicals LLC. Basic Protocol 1 : Processing, combining, and visualizing two DDA libraries Basic Protocol 2 : Parallel processing and combination of multiple DDA libraries Basic Protocol 3 : Downstream processing, comparison, and visualization of DIA report files